2014
DOI: 10.1371/journal.pone.0102951
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Whole-Cell Biocatalyst for Acetoin Production with NAD+ Regeneration System through Homologous Co-Expression of 2,3-Butanediol Dehydrogenase and NADH Oxidase in Engineered Bacillus subtilis

Abstract: Acetoin (3-hydroxy-2-butanone), an extensively-used food spice and bio-based platform chemical, is usually produced by chemical synthesis methods. With increasingly requirement of food security and environmental protection, bio-fermentation of acetoin by microorganisms has a great promising market. However, through metabolic engineering strategies, the mixed acid-butanediol fermentation metabolizes a certain portion of substrate to the by-products of organic acids such as lactic acid and acetic acid, which cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 42 publications
0
46
0
Order By: Relevance
“…Expression of KSDD was also detected by western blotting with a mouse monoclonal anti-His6 antibody. The samples were treated as described by Bao et al [26], and the bands were detected by chemiluminescence with luminol and peroxide with the help of a Bio-Rad Chemidoc XRS. Bradford method was employed to determine the protein concentration by using BSA as standard protein [27].…”
Section: Sds-page Analysis and Determination Of Protein Concentrationmentioning
confidence: 99%
“…Expression of KSDD was also detected by western blotting with a mouse monoclonal anti-His6 antibody. The samples were treated as described by Bao et al [26], and the bands were detected by chemiluminescence with luminol and peroxide with the help of a Bio-Rad Chemidoc XRS. Bradford method was employed to determine the protein concentration by using BSA as standard protein [27].…”
Section: Sds-page Analysis and Determination Of Protein Concentrationmentioning
confidence: 99%
“…The AD conversion rate decreased when the pH shifted away from the optimal pH, which indicated that the KSDD enzyme could only retain limited activity in these pH conditions. Temperature is also an important factor in whole‐cell catalytic processes, and affects enzyme activity and cellular maintenance . Reactions were carried out at temperatures ranging from 20 to 50°C and used to determine the optimal temperature.…”
Section: Optimization Of Process Conditions For Ksdd Productionmentioning
confidence: 99%
“…Among all these approaches, due to its mild and simple reaction conditions, high catalytic efficiency and selectivity, environmental compatibility, and easy purification process, enzymatic synthesis using KSDD to catalyze AD dehydrogenation to ADD is a favorable way . With the constant improvement in environmental protection consciousness and the further development of green technology, non‐pollution and non‐toxic biological technology has inevitably become the main direction of industrial development . So far, several microorganisms including Mycobacterium , Rhodococcus , Nocardia , and Arthrobacter were found capable of transforming AD to ADD .…”
Section: Introductionmentioning
confidence: 99%
“…To achieve a higher product yield, fed‐batch strategies could efficiently improve the production of the aimed products (Bao et al . ; Shao et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…With the constant improvement in environmental protection consciousness and further development of green technology, nonpollution and nontoxic biological technology has inevitably become the main direction of industrial development (Bao et al . ; Shao et al . ).…”
Section: Introductionmentioning
confidence: 99%